Description of a new brachypterous species of Phelotrupes Jekel, 1866 from Xizang, China, with additional records of Geotrupes Latreille, 1797 (Coleoptera: Geotrupidae) - Luo, Yi-Ping; Lu, Yuan-Yuan; Král, David (Zootaxa, 2026)
Phelotrupes (s. str.) brachypterus sp. nov. is described from Zayü County, Xizang, China. The new species is notably similar to the also brachypterous species P. (s. str.) imurai (Masumoto, 1995). Diagnostic characters of the new species, including the male genitalia, are illustrated. The first provincial records of Geotrupes (s. str.) corinthius Fairmaire, 1886 from Shaanxi and Xizang, G. (Glyptogeotrupes) castanipennis (Reitter, 1887) from Xizang and G. (Glyptogeotrupes) genestieri (Boucomont, 1905) from Yunnan and Xizang are reported. An annotated checklist of the family Geotrupidae recorded from Xizang, China, is also provided.